(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj MHGfj HGdCUZQjf GdbdH hGddSGf s
(3BNQgG (B:s
(3Ef GdaNGQ hGdYdG EQKc ef Ohf GdedG Je GdcJGH fSNoG HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HChdgG Jedc eDQN SfI (B843(3g`s
(3HgG fXGe GdJYbjHIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdKGfjI eY GNJdGa aj HYV GdCdaGXs
(3fSNI NGeSI s
(3JHUQI GdYfhGf (B:s
(3fXe s
Keywords: (3GdCOHs